Living in negotiation: patients’experiences of being in the diagnostic process of COPD - Lindgren,Sari; Storli,Sissel Lisa; Wiklund-Gustin,Lena (International Journal of Chronic Obstructive Pulmonary Disease, 2014)
Sari Lindgren,1,2 Sissel Lisa Storli,3 Lena Wiklund-Gustin4,51Department of Health and Care Sciences, Faculty of Health Sciences, UiT Arctic University of Norway, Tromsø, Norway; 2Faculty of Health and Society, Narvik University College, Narvik, Norway; 3Department of Health and Care Sciences, Faculty of Health Sciences, UiT Arctic University of Norway, Tromsø, Norway; 4Faculty of Health and Society, Narvik University College, Narvik, Norway; 5School of Health, Care and Social Welfare, Mälardalen University, Västerås, SwedenPurpose: To illuminate patients’ lived experiences of going through the process of being diagnosed with chronic obstructive pulmonary disease (COPD).Patients and methods: A phenomenological-hermeneutic analysis was applied in the interpretation of interviews with eight persons diagnosed with mild or moderate COPD.Results: One main theme ‘living in negotiation’, and three themes ‘living with a body out of step with the diagnosis’, ‘dealing with the past’, and ‘being challenged by the future’ reflected the process participants were living through in their quest for acceptance and a new balance in life. Participants found that the diagnostic processes were confusing, and that the diagnosis itself was ‘a slap in the face’. Unclear messages gave rise to fluctuating between an understanding of the condition as ‘not too severe’, insecurity, and fear. Shame and guilt related to the diagnosis had origins in the past, and in combination with the idea of ‘chronic’ the COPD diagnosis interfered with the present moment and gave rise to uncertainty for the future. The understanding of the present is related to negotiations not only with the past, but also with the future. Thus temporal aspects of the diagnosis are of great significance for the process of finding acceptance.Conclusion: Regardless of disease severity, the diagnosis seems to be a breakdown of life, which puts life itself at stake. Medical professionals should be aware that the way the diagnosis is disclosed and communicated has considerable ...